Using a mobile application to detect health needs among children and adolescents who are newly arrived migrants in Europe. (13th November 2018) - Rath, B; Swenshon, S; Haase, K; Szeles, T; Jung, C; Jacobi, F; Myles, P
Abstract: Background: Unprecedented numbers of migrants have arrived in Europe, including children and adolescents. Little is known about their unique health needs. Prospective data collection has been sparse. Mobile applications may help to facilitate global health surveillance. Methods: A pre-validated survey instrument was converted into a mobile application covering self-reported exposures and disruptions of healthcare before/during migration, communicable and non-communicable diseases. Participation was voluntary, anonymous and confidential. Results: Data were obtained from 405 migrant children and adolescents in Berlin, Germany, between 7 October 2015 and 15 March 2016 (median age 19 years, range: 1–24; 80.7% males) with the majority from Syria (62.5%), Afghanistan (9.1%) and Iraq (8.2%). In total, 55% were without family, 64% registered asylum-seekers with access to healthcare; 54% had seen a doctor since arrival, with colds or respiratory complaints (37.5 and 13.6%), followed by pain (26.7%) gastrointestinal (12.4%) and skin problems (11.1%). Underlying conditions were reported in 15.6%, predominantly asthma. Overall, 73% reported being up-to date on immunizations, but only 22% held a vaccination record with 46.4% having lost it during migration. Conclusions: The lack of medical and immunization records among newly arrived migrants provides a challenge to healthcare systems. Mobile applications offer rapid screening tools in times of crisis, helping stakeholders with timely information.